Spirituality at Workplace and Job Satisfaction in an ASEAN context - Fanggidae, Roland Epafras (JOURNAL OF ECONOMIC SCIENCE, 2015)
Global competition between countries both economic and human resources will increase significantly. Agreements ASEAN countries to establish the ASEAN Free Trade Area (AFTA) the creation of global and regional competition. To deal with this phenomenon, the necessary transformation in the lives of the people, companies, and individuals. If you look at the success of Japan and China are becoming the new economic power, then the answer to this phenomenon is the "Character". Strong and noble character rooted in the culture of the nation into a unique differentiation. In the context of ASEAN actually has a very unique role in shaping the character of the nation, where the ASEAN countries is a religious nation. This can be a major capital in the formation of national character and can be implemented in the work so that it becomes its own power. Spirituality workplace consisting of dimension Meaningful work, Sense of community, alignment with the organizations values and Job as calling have a relationship with Job Satisfaction. Spirituality workplace can create a work environment that is humanistic, so that employees more creative and have high spirits.